A DNA helicase induced by herpes simplex virus type 1. - Crute, J J (1988)
We have identified and partially purified a DNA-dependent ATPase that is present specifically in herpes simplex virus type 1-infected Vero cells. The enzyme which has a molecular weight of approximately 440,000 differs from the comparable host enzyme in its elution from phosphocellulose columns and in its nucleoside triphosphate specificity. The partially purified DNA-dependent ATPase is also a DNA helicase that couples ATP or GTP hydrolysis to the displacement of an oligonucleotide annealed to M13 single-stranded DNA. The enzyme requires a 3' single-stranded tail on the duplex substrate, suggesting that the polarity of unwinding is 5'----3' relative to the M13 DNA. The herpes specific DNA helicase may therefore translocate on the lagging strand in the semidiscontinuous replication of the herpes virus 1 genome.